Strategic Activation of Management Information Systems to Eliminate Political Corruption in State Institutions: Applied research in the facilities of the Iraqi Ministry of Oil - Enas Diaa Mahdi (QALAAI ZANIST JOURNAL, 2023)
Administrative information systems are one of the foundations on which the work mechanisms of governmental and private organizations are based, due to the accurate capabilities they provide through their data and statistics, which prevent institutions from falling into administrative errors and problems, which often translate into administrative and political corruption. Given the accuracy of ICT financial and economic transactions as the basis for management information systems, it can directly contribute to increasing the level of political reform in state ministries, reducing their administrative and political corruption, and reducing their administrative and political corruption. The attempt was made by emphasizing a set of connected studies The introductory data on the two variables of , to demonstrate an introductory argument about the fact that there is a positive correlation between the development of the government system and the increase in political reforms of state institutions, will be taken through the detailed exploration phase.And, because political corruption in state institutions, particularly public sector institutions, Equally important for policy and government research, the study attempts to establish a logical link between the development of e-government work leading to the application of management information systems to elements of government agencies and their adoption as a regular format in their operations, and the relationship between the two connect. Additionally, the advanced with impartial supervision mechanism that the electronic government offers substantially eliminates the flaws in the political and administrative control systems. bias and prejudice in assessing how well state institutions work. As a result, the research emphasizes the attempt to prove a fundamental hypothesis related to the existence of a relationship between the improvment of electronic information systems and the elimination of political corruption in state ministries, by emphasizing a set of real data that related with the two research variables, which will be explained in articals of the research.